COMMUNICATION AS A PSYCHOLINGUISTIC PHENOMENON (Scientific journal of the Fergana State University, 2024)
This article emphasizes that it is the psycholinguistic study of communication that makes it possible to highlight aspects of speech activity related to the human factor, the mental and mental state of a person. The realization of speech unity is presented on the examples of research within the framework of discourse – the process of speech communication, the activities of communicants to exchange opinions and interact with each other. At the manipulative level, the manifestation of interest in the weaknesses of the interlocutor is analyzed, since at the same time, for the participant of communication, the interlocutor appears to be a rival, tries to overcome him, while the manipulator consciously or unconsciously seeks to overcome the interlocutor, to win over him, pursuing his own interests.